ChemInform Abstract: Regio‐ and Enantioselective Cobalt‐Catalyzed Reductive [3 + 2] Cycloaddition Reaction of Alkynes with Cyclic Enones: A Route to Bicyclic Tertiary Alcohols. Issue 11 (8th March 2013) - Wei, Chu‐Hung; Mannathan, Subramaniyan; Cheng, Chien‐Hong
Abstract The bridged alcohol systems are synthesized by reductive [3 + 2] cycloaddition of cyclic enones with alkynes in the presence of Co salts.